Sediment denitrification in the Mira estuary salt marshes - Lança, M.J. (2012)
Sediment denitrification is a microbial process that converts dissolved inorganic nitrogen present in sediment porewaters to nitrogen gas, which is lost to the atmosphere. Sediment denitrification was determined as a flux of nitrogen gas from intact sediments incubated in gas-tight chambers. The present technique allows for the direct measurement od denitrification in undisturbed sediment cores under ambient conditions of oxygen, dissolved nutrients and temperature. Nitrogen gas flux was measured from Spartina maritima sediments taken from the Mira estuary salt marshes in southern Portugal, over six month period. DNF rates ranged from 0.42 to 20.86 mmoles N2.m2.day. Lowest rates were obtained during spring months when salt marshes presented a peak export of dissolved inorganic nitrogen to the Mira estuary. The lowest rate obtained in April seems to be related with the dissolved inorganic nitrogen export period that characterized the spring months in the Mira salt marshes. The highest rate was measured in July. During summer months, the flux of nitrate out of the sediments reached the higher values. This result suggests that nitrate produced by nitrification in the sediments during this time of the year appears to be an important substarte for DNF in the Mira salt marshes. In summer, there was also a substantial import of ammonium and nitrate into marsh. Although water column nitrate concentrations were not high, this fact does not eliminate the possibility that some nitrate from the water column enters the sediment and is denitrified.